Characterization of elderly people with an intestinal stoma at a reference center in the state of Bahia (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To characterize the elderly patients with intestinal stoma, enrolled in a Reference Center of the public health network of the state, regarding sociodemographic and clinical aspects. Method: This is a cross-sectional descriptive study with a sample of 33 elderly patients with intestinal stoma who met the inclusion criteria. Data were extracted from the medical record, interview and evaluation of the stoma and surrounding skin, analyzed through descriptive statistics. Results: patients underwent surgery in public and private hospitals, 54.5% were female, 51.6% married or in stable union, mean age was 68.03 (± 7.2) years, 69.7% had cancer as a cause of the stoma, 66.7% were temporary and 81.8% were colostomies. There was a predominance of stomas with a regular and round shape, diameter between 10 and 64 mm and a mean protrusion of 2.79 mm (± 5.1), use of a drainage bag with a cut greater than the stoma, 51.5% for stoma and device care. Conclusion: the study allowed to identify the profile of the elderly with intestinal stoma, which will allow the adjustment of the specialized assistance planning and the provision of collecting equipment and adjuvants in the context of the state.
Keywords: Colostomy; Ileostomy; Health of the elderly; Health profile; Enterostomal therapy.